Asylum seekers' experiences with quarantine after arriving in Germany during the COVID-19 pandemic. (20th October 2021) - Rast, E; Perplies, C; Biddle, L; Bozorgmehr, K
Abstract: Background: During the COVID-19 pandemic, newly arriving asylum seekers undergo mandatory quarantine in many European countries. Quarantine is likely to amplify pre-existing strains associated with asylum seeking, including limited autonomy and barriers for care-seeking. Our objectives were a) to elicit asylum seekers' experiences with quarantine regarding their mental health and needs and b) to explore how they assess the measure. Methods: We conducted 9 semi-structured interviews with asylum seekers in a German reception centre (July-December 2020). Individuals with quarantine experience who spoke German, English or French were invited to participate. The interviews were recorded, transcribed and analysed thematically with an inductive-deductive approach. Funding: German Federal Agency for Health Education (BZgA). Results: The participants (2 women, 6 men and a couple from Syria, Algeria, Yemen, Bangladesh and Cameroon) experienced the quarantine as a difficult situation and described feeling locked-in and bored. Obsessive thinking, loneliness, sleeping problems and feelings of abandonment were repeatedly reported. Unmet basic needs (e.g. special foods, cleaning tools, shampoo, Wi-Fi) and unclarity about access to social or emergency help further impaired wellbeing in some cases. In view of negative PCR test results, the rationale of mandatory quarantine was questioned by some. Assessments of the quarantine varied: Some favoured individual responsibility, physical distancing and hygiene measures over quarantine, while others considered it necessary for health protection despite the strains entailed. Conclusions: Quarantine can be a considerable stressor for asylum seekers. In this explorative study, shortcomings in the provision of daily necessities and information were visible. Potential adverse impacts of quarantine on wellbeing should be minimised through ensuring its comprehensibility, the supply of daily needs and low-threshold access to psychosocial support. Key messages: Quarantine can be a significant stressor for newly arriving asylum seekers. Quarantine-induced stress should be minimised through appropriate information, the provision of daily necessities and psychosocial support.